2018
DOI: 10.1093/hmg/ddy040
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed microRNAs in the aqueous humor of patients with exfoliation glaucoma or primary open-angle glaucoma

Abstract: Both exfoliation glaucoma (XFG) and primary open-angle glaucoma (POAG) have been linked to decreased conventional outflow of aqueous humor (AH). To better understand the molecular changes in the AH content under such conditions, we analyzed the miRNA profiles of AH samples from patients with POAG and XFG compared to non-glaucoma controls. Individual AH samples (n = 76) were collected from POAG and XFG patients and age-matched controls during surgical procedure. After RNA extraction, the miRNA profiles were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 88 publications
3
77
2
3
Order By: Relevance
“…RNA quantity was measured using the Tecan microplate reader M200 (Tecan Group Ltd., Mannedorf, Zurich, Switzerland), and RNA quality was evaluated using the Agilent Bioanalyzer 2100 with RNA Pico Chips. 100 ng of total RNA was used to measure the expression of 800 pre-selected human miRNAs using the nCounter Human v3 miRNA expression assay kit from NanoString Technologies (Seattle, WA, USA), as previously described (31). After specific sample preparation and overnight hybridization, digital readouts of the relative miRNA abundance were obtained, translating to miRNA expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA quantity was measured using the Tecan microplate reader M200 (Tecan Group Ltd., Mannedorf, Zurich, Switzerland), and RNA quality was evaluated using the Agilent Bioanalyzer 2100 with RNA Pico Chips. 100 ng of total RNA was used to measure the expression of 800 pre-selected human miRNAs using the nCounter Human v3 miRNA expression assay kit from NanoString Technologies (Seattle, WA, USA), as previously described (31). After specific sample preparation and overnight hybridization, digital readouts of the relative miRNA abundance were obtained, translating to miRNA expression.…”
Section: Methodsmentioning
confidence: 99%
“…The raw data RCC files produced by nCounter were processed with the NanoString nSolver 3.0 software using a previously described analysis pipeline (31). Each sample was run through several quality control checks before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…By conducting a microarray analysis of the differential expression of miRNA in the aqueous humour of glaucoma patients, several glaucoma-related extracellular miR-NAs have been identified (Tanaka et al 2014). Further investigation, through analysing both POAG and XFG patients, showed that three miR-NAs between POAG and control, five miRNAs between XFG and controls and one miRNA (miR-302d-3p) between POAG and XFG exhibited significant differences in expression (Drewry et al 2018). These miRNAs are likely to be involved in some glaucoma pathways including focal adhesion, tight junctions and TGF-b signalling pathways (Drewry et al 2018).…”
Section: Epigenetic Factors: Mirnamentioning
confidence: 99%
“…Further investigation, through analysing both POAG and XFG patients, showed that three miRNAs between POAG and control, five miRNAs between XFG and controls and one miRNA (miR‐302d‐3p) between POAG and XFG exhibited significant differences in expression (Drewry et al. ). These miRNAs are likely to be involved in some glaucoma pathways including focal adhesion, tight junctions and TGF‐ β signalling pathways (Drewry et al.…”
Section: Epigenetic Factors: Mirnamentioning
confidence: 99%
See 1 more Smart Citation